Comparing the effects of vitamin E tocotrienol-rich fraction supplementation and α-tocopherol supplementation on gene expression in healthy older adults - Siti Madiani Abdul Ghani; Jo Aan Goon; Nor Helwa Ezzah Nor Azman; Siti Nor Asyikin Zakaria; Zalina Hamid; Wan Zurinah Wan Ngah (Clinics, 2019)
OBJECTIVES This study aims to compare the differential gene expression resulting from tocotrienol-rich fraction and α-tocopherol supplementation in healthy older adults. METHODS A total of 71 eligible subjects aged 50 to 55 years from Gombak and Kuala Lumpur, Malaysia, were divided into three groups and supplemented with placebo (n=23), α-tocopherol (n=24) or tocotrienol-rich fraction (n=24). Blood samples were collected at baseline and at 3 and 6 months of supplementation for microarray analysis. RESULTS The number of genes altered by α-tocopherol was higher after 6 months (1,410) than after 3 months (273) of supplementation. α-Tocopherol altered the expression of more genes in males (952) than in females (731). Similarly, tocotrienol-rich fraction modulated the expression of more genes after 6 months (1,084) than after 3 months (596) and affected more genes in males (899) than in females (781). α-Tocopherol supplementation modulated pathways involving the response to stress and stimuli, the immune response, the response to hypoxia and bacteria, the metabolism of toxins and xenobiotics, mitosis, and synaptic transmission as well as activated the mitogen-activated protein kinase and complement pathways after 6 months. However, tocotrienol-rich fraction supplementation affected pathways such as the signal transduction, apoptosis, nuclear factor kappa B kinase, cascade extracellular signal-regulated kinase-1 and extracellular signal-regulated kinase-2, immune response, response to drug, cell adhesion, multicellular organismal development and G protein signaling pathways. CONCLUSION Supplementation with either α-tocopherol or tocotrienol-rich fraction affected the immune and drug response and the cell adhesion and signal transduction pathways but modulated other pathways differently after 6 months of supplementation, with sex-specific responses.